Effects of cleaning sports mouthguards with ethylene-vinyl acetate on oral bacteria - Hiroki Hayashi; Yoshikazu Naiki; Masahiro Murakami; Akihiro Oishi; Rihoko Takeuchi; Masayoshi Nakagawa; Suguru Kimoto; Yoshiaki Hasegawa; Akizumi Araki (PeerJ, 2022)
Background Sports mouthguards, worn in the oral cavity to prevent sports injuries, are constantly exposed to various microorganisms that cause oral infections. Hence, the optimal cleaning methods for sports mouthguards have been thoroughly examined. In this study, we evaluated the efficiency of cleaning effects with a mouthguard cleaner (MC) on microbial biofilm formation in sports mouthguards in vitro and in vivo. Methods We evaluated the cleaning effects of the discs produced by ethylene-vinyl acetate (EVA) on bacterial biofilms formed by the commensal bacterium Streptococcus oralis, the cariogenic bacterium Streptococcus mutans, and the opportunistic pathogen Staphylococcus aureus in vitro. EVA discs with biofilm were subjected to sterile distilled water (CTRL) and ultrasonic washing (UW), followed by treatment with MC and sodium hypochlorite (NaClO) as positive controls. Thereafter, the viable bacterial cell counts were determined. The bacteria adhering to the sheets before and after the treatment were observed under an electron microscope. The degree of cleanliness and measurement of viable microbial cell counts for total bacteria, Streptococci and Candida, opportunistic fungi, were evaluated on the used experimental sports mouthguards with and without UW and MC treatment in vivo. Results The number of bacterial cells significantly decreased against all the tested biofilm bacteria upon treatment with MC, compared with CTRL and UW. Electron microscopy analysis revealed the biofilm formation by all bacteria on the EVA discs before cleaning. We observed fewer bacteria on the EVA discs treated with MC than those treated with CTRL and UW. Furthermore, the degree of cleanliness of the used experimental sports mouthguards cleaned using MC was significantly higher than that of the CTRL-treated mouthguards. Moreover, the viable microbial cell counts on the used experimental sports mouthguard were considerably lower than those on the CTRL ones. Conclusion The cleaning effect of MC against oral bacteria was more effective than that of UW. MC treatment might have a potential future application as a cleaning method for sports mouthguards to protect athletes from oral infection.